Inverse dual converter (IDC) for high power DC-DC applications - Ehsani, M.; Husain, I.; Bilgiç, Mehmet Oruç (IEEE, 1993)
A family of DC-DC converters suitable for high-power applications is introduced. The inverse dual converter (IDC) is capable of continuous voltage step-up or step-down control over a wide range of and without the need of a transformer. Experimental verification of the analysis is given for the simple single-phase IDC. Some of the more sophisticated members of the IDC family are described, and their characteristics and possible application, are mentioned.
Keywords: DC-DC power converters; Switching converters; Magnetic resonance; Voltage control; Circuit faults; Topology; Resonant frequency; Magnetic separation; Filters; Switching frequency